Research on Thermodynamic Properties of the CO2 Medium During Phase Transition Excited by Energetic Agent - SHEN Zhiqiang; XIA Jun; ZHANG Fanzhen; YANG Lijun (工程科学与技术)
ObjectiveAccurately prediction of the phase transition process of liquid (or liquid-vapor equilibrium state) CO2 working fluid sealing in sturdy containers excited by energetic agents is of great significance for the in-depth application of CO2 phase transition expanding (or fracturing) technology in large-scale network precision blasting and payload propulsion. Although sophisticated numerical calculations based on combustion and heat transfer theory using computational fluid dynamics (CFD) simulation software can provide an option for this problem, the process is time-consuming, which is often unacceptable for engineering applications and relative mechanical device initial design. A zero-dimension theory prediction model is established in our work and can be used to obtain the thermodynamic parameters of the CO2 working fluid during exciting process more easily.MethodsBased on the geometric combustion hypothesis of energetic agents and the thermodynamic conservation laws of the system, a thermodynamic performance prediction model for the phase change process of CO2 working medium excited by energetic agents was established, and the classical Runge-Kutta step-by-step integration algorithm was used to get numerical solution. Due to the complex phase change characteristics of CO2 working fluid during the stimulation process and a necessary reliability demand of the state equation for the working fluid in relatively wide range of temperatures and pressures especially the supercritical state, the SW96 state equation based on the specific Helmholtz free energy recommended by NIST was adopted to describe the thermal properties of CO2 working fluid in the numerical calculation process. The primary combustion products of the energetic agents are CO₂, with a mass fraction exceeding 60%. Additionally, the mass of the energetic material is significantly less than that of the CO₂ working fluid excited within the sealed container. In order to find the best balance position between the acceptable computational cost and prediction accuracy of the zero-dimensional theoretical model, the following additional assumption were introduced. Such the gaseous combustion products of the energetic agent are all equivalently assumed to be CO2 by mass, and the heat released by the combustion of the energetic agent in each time increment step is instantly absorbed by the combustion products and the original CO2 working fluid together without any relaxation. To validates the effectiveness of the prediction model, a series of experimental studies on the phase transition of CO2 working fluid excited by new types of energetic agents were designed and carried out. Before each test, a cylindrical energetic agent was securely placed on one end face inside the sealed container. Subsequently, the container was filled with CO2 working fluid to a certain pressure using a CO2 charging machine. After sealing the container, the mass of the working fluid was measured, and the signal cables of the excitation controller and pressure sensor were connected. At the start of the test, the excitation controller issued an ignition signal, which immediately ignited the energetic agent. Simultaneously, a data acquisition command was sent to the ultra-dynamic signal testing and analysis system. The energetic agent burned rapidly and released heat, causing the CO2 working fluid to absorb heat and undergo a phase change. The pressure inside the container risen quickly until the agent was completely burned. The dynamic data acquisition instrument and a laptop were used to collect and record the pressure data inside the sealed container during this process, and the data was filtered before further analysis.Results and DiscussionsBy comparing the measured dates of the working fluid pressure rising time (i.e., the time from the initial pressure to the peak pressure inside the container) and the peak pressure with the numerical calculated values of the theoretical prediction model for 4 different energetic agent mass cases namely 30, 40, 50 and 60 g, it is shown that the relative errors of the working fluid pressure rising time and peak pressure in the sealed container are less than 8% and 7%, respectively. The calculation results of the pressure variation history indicate that, after the excitation process starts, the working fluid pressure rising process could be divided into three stages: slow rise, rapid rise, and a slowdown in growth approaching the peak pressure. Among them, the first and third stages have relatively short durations, while the second stage has a longer duration and the pressure change is approximately linear with respect to time. To investigate the influence of the ignition position of the cylindrical charge on the thermodynamic parameter changes during the excitation process, in addition to the center of the end face of the cylindrical charge, the ignition device was also placed at the midpoint of the charge axis and the quarter-point between the midpoint of the axis and the end face. Compared to end-face ignition, central ignition of the cylindrical charge can reduce the pressure rising time by 39.73%. This phenomenon occurs because moving the ignition position from the end face to the interior of the charge increases the effective combustion area of the charge. As a result, the heat released per unit time is enhanced, which in turn accelerates the pressure rise rate of the CO₂ working fluid. While keeping the mass of the charge constant at 60 g, the influence of the cylindrical charge shape on the excitation process was then investigated by adjusting the radius r and length h of the cylindrical charge.ConclusionsThe high accuracy and feasibility of the prediction model have been thoroughly validated through comparisons between numerical calculations and experimental results. The initial ignition position and geometric shape of the energetic agents have a significant impact on the phase transition process of CO2 working fluid. As the ignition position moves from the center of the end face along the axis to the inside of the agent, the working fluid pressure rising time is significantly shortened. Meanwhile, the characteristics of the working fluid pressure rising process are also closely related to the geometric shape of the energetic agent. It can be concluded that the thermodynamic state of CO2 working fluid during the excitation process can be precisely controlled by reasonably designing the shape and ignition position of the energetic agent.